Business Risk Momed in Banking Companies Listed On The Indonesia Stock Exchange With Digital Transformation on Financial Perfomance - Razif, Muhammad; Masdupi, Erni (Kirana Publisher (KNPub), 2026)
This study aims to analyze the impact of digital transformation on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with business risk as a mediator and moderator. A descriptive quantitative survey was implemented to collect data from annual reports of 229 banking companies. The data analysis utilized Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that digital transformation positively influences financial performance, with business risk playing a significant mediating role in the relationship between digital transformation and financial performance. However, business risk did not moderate the effect of digital transformation on financial performance, as no significant interaction was found. These results emphasize the importance of managing business risk as a mediator to enhance the effectiveness of digital transformation in improving financial performance in the banking sector.